If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -5x = 1 + -1x Solving 13 + -5x = 1 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 13 + -5x + x = 1 + -1x + x Combine like terms: -5x + x = -4x 13 + -4x = 1 + -1x + x Combine like terms: -1x + x = 0 13 + -4x = 1 + 0 13 + -4x = 1 Add '-13' to each side of the equation. 13 + -13 + -4x = 1 + -13 Combine like terms: 13 + -13 = 0 0 + -4x = 1 + -13 -4x = 1 + -13 Combine like terms: 1 + -13 = -12 -4x = -12 Divide each side by '-4'. x = 3 Simplifying x = 3
| 3/8+1/4x=7/16 | | x^2=25/289 | | 2(x-5)=60 | | -3y+7=5 | | (x/5)+7=11 | | 2-2-(-7)= | | 52=4d | | 60=5y | | 5(-2n+4)= | | (-8)+2+1= | | 8.6=n+2.2 | | 27=3x-15+18 | | -5(x-2)+3x=10-4(2x-5)+6 | | 2/11n=-3/8 | | 3x-3=3(x+1)+6 | | X+3x/120 | | 2m-3=-8m+27 | | x^4-2x^3+15x^2=0 | | -1-5x=-36 | | Z+5=8 | | 20-13=20+9x | | 1.3+0.5x=-3.14 | | 8^2+9(12/3*2)-7 | | 16/8=n/36 | | (3)(2)/2-4 | | -6x+1=7-6x | | 153/24 | | 9(v+1)-3v=2(3v+1)-5 | | 1.3c=3c+2.8 | | B-8+6b=24 | | 3(x-3)=6x-18/2 | | 5(2.4-4)=8 |